Incidence and risk factors of adjacent segment disease following posterior decompression and instrumented fusion for degenerative lumbar disorders. Issue 5 (February 2017) - Wang, Hui; Ma, Lei; Yang, Dalong; Wang, Tao; Liu, Sen; Yang, Sidong; Ding, Wenyuan
Abstract : Abstract: The purpose of this study was to explore incidence and risk factors of adjacent segment disease (ASD) following posterior decompression and instrumented fusion for degenerative lumbar disorders, and hope to provide references in decision making and surgical planning for both spinal surgeon and surgically treated patients. By retrieving the medical records from January 2011 to December 2013 in our hospital, 237 patients were retrospectively reviewed. According to the occurrence of ASD at follow up, patients were divided into 2 groups: ASD and N-ASD group. To investigate risk values for the occurrence of ASD, 3 categorized factors were analyzed statistically: Patient characteristics : age, sex, body mass index (BMI), bone mineral density (BMD), duration. Surgical variables: surgical strategy, number of fusion level, surgery segment, surgery time, blood loss, intraoperative superior facet joint violation. Radiographic parameters : preoperative lumbar lordosis, preoperative angular motion at adjacent segment, preoperative adjacent segment disc degeneration, preoperative paraspinal muscle degeneration. Postoperative ASD was developed in 15 of 237 patients (6.3%) at final follow up. There was no statistically significant difference between the 2 groups in patient characteristics of age, sex composition, BMD, duration, while the BMI was higher in ASD group than that in N-ASD group. There was no difference in surgical variables of surgical strategy, number of fusion level, surgery segment, surgery time, blood loss, while intraoperative superior facet joint violation was more common in ASD group than that in N-ASD group. There was no difference in radiographic parameters of preoperative lumbar lordosis, preoperative paraspinal muscle degeneration, while preoperative adjacent segment disc degeneration were more severe in ASD group than that in N-ASD group. The Logistic regression analysis revealed that, BMI >25 kg/m 2, preoperative disc degeneration, and superior facet joint violation were independently associated with ASD. In conclusion, higher BMI, preoperative disc degeneration at adjacent segment and intraoperative superior facet joint violation are risk factors for ASD. Patients who are overweight or obesity and with preoperative disc degeneration at adjacent segment should be fully informed the risk of ASD. For surgeons, it is essential to prevent superior facet joint violation in pedicle screw insertion procedure.